Splenic T1ρ as a noninvasive biomarker for portal hypertension. Issue 3 (19th February 2020) - Hectors, Stefanie J.; Bane, Octavia; Stocker, Daniel; Carbonell, Guillermo; Lewis, Sara; Kennedy, Paul; Schiano, Thomas D.; Thung, Swan; Fischman, Aaron; Taouli, Bachir
Abstract : Background: There is a need for noninvasive methods for the diagnosis and monitoring of portal hypertension (PH). Purpose: To 1) assess the correlation of liver and spleen T1 and T1ρ measurements with portal pressures in patients with chronic liver disease, and 2) to compare the diagnostic performance of the relaxation parameters with radiological assessment of PH. Study Type: Prospective. Subjects: Twenty‐five patients (M/F 16/9, mean age 56 years, range 21–78 years) undergoing portal pressure (hepatic venous pressure gradient [HVPG]) measurements. Field Strength/Sequence: 1.5T abdominal MRI scan, including T1ρ and T1 mapping. Assessment: Liver and spleen T1ρ and T1, radiological PH score, and (normalized) spleen length were evaluated. Statistical Tests: Spearman correlation of all MRI parameters with HVPG was assessed. The diagnostic performance of the assessed parameters for prediction of PH (HVPG ≥5 mmHg) and clinically significant PH (CSPH, HVPG ≥10 mmHg) was determined by receiver operating characteristic (ROC) analysis. Results: The mean HVPG measurement was 7.8 ± 5.3 mmHg (PH, n = 18 [72%] including CSPH, n = 9 [36%]). PH score, (normalized) spleen length and spleen T1ρ significantly correlated with HVPG, with the strongest correlation found for spleen T1ρ ( r = 0.613, P = 0.001). Spleen T1ρ was the only parameter that showed significant diagnostic performance for assessment of PH (area under the curve [AUC] 0.817, P = 0.015) and CSPH (AUC = 0.778, P = 0.024). Normalized spleen length also showed significant diagnostic performance for prediction of CSPH, with a slightly lower AUC (= 0.764, P = 0.031). The radiological PH score, T1ρ and T1 of the liver and T1 of the spleen, did not show significant diagnostic performance for assessment of CSPH ( P > 0.075). Data Conclusion: Spleen T1ρ showed a significant correlation with portal pressure and showed improved diagnostic performance for prediction of CSPH compared to radiological assessment. These initial results need confirmation in a larger cohort. Level of Evidence: 1 Technical Efficacy Stage: 2 J. Magn. Reson. Imaging 2020;52:787–794.